From nanospheres to micelles: simple control of PCL-g-PEG copolymers' amphiphilicity through thiol–yne photografting1. Issue 28 (28th July 2015) - Al Samad, Assala; Bakkour, Youssef; Fanny, Coumes; El Omar, Fawaz; Coudane, Jean; Nottelet, Benjamin
<x xml:space="preserve">Abstract</x> A unique combination of polyester post-polymerization modification and photoradical thiol–yne addition is reported for the synthesis of amphiphilic degradable graft copolymers with controlled compositions, used to prepare micelles or nanospheres.